Georgia : 2018 Article IV Consultation, Second Review under the Extended Fund Facility Arrangement, and Request for Modification of a Quantitative Performance Criterion. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that the macroeconomic performance in Georgia since the global financial crisis has been positive. Growth was higher than that in most peers. The banking sector has remained stable, and foreign reserves have increased. After two years of sluggish growth, following the 2014 regional slowdown, growth has picked up and the external position strengthened. Supported by external demand and buoyant consumption, real GDP grew 5 percent in 2107. The near-term outlook has improved moderately and the output gap is expected to close gradually in 2019-20. Over the medium to long term growth is expected to accelerate moderately and external vulnerabilities to decrease, thanks to the dividends from structural reforms.